Demystifying Statistical Tools and Treatment of Data in Research - Mchi, Akaawase Alexander; Odigwe, Moses; Ojoh, Collins (Journal of Multidisciplinary Research Advancements, 2025)
This article focuses on demystifying statistical tools and data treatment in research. It began with a brief explanation of statistical concepts, data collection, and measurement scales, highlighting common errors in the use and selection of statistical tools. There are multiple statistical tools available for researchers. Some statistical tools are simple, whereas others are complex and highly purpose-specific. The article presents an overview of basic statistical tools necessary for research and explains when to use them to avoid manipulating analyses to achieve statistical significance. The article further identifies the conditions under which the choice of statistical tools for comparisons and relationships should be made if the results are to be meaningful.